A dynamic model of the relationship between income and financial satisfaction: evidence from Ireland - Newman, Carol; Delaney, Liam; Nolan, Brian (Economic & Social Studies, 2008)
The link between income and subjective satisfaction with one?s financial situation is explored in this paper using a panel analysis of 1,998 individuals tracked through the course of the boom period in Ireland, 1994-2001. A dynamic ordered probit model which incorporates state dependence and controls for correlated individual effects and the initial conditions problem is applied. The impact of the level of household income, the time-path of income and deviations of individual income from reference group income and household income are all considered. To the extent that income influences financial satisfaction, there is strong evidence from this paper that the level of household income has the most important effect but this effect is lessened once persistence in the data is controlled for and is diminishing at higher income levels. Controlling for income and socio-economic characteristics, the positive deviations of household income from reference group income are found to have a positive effect on financial satisfaction as are positive deviations of individual income from household income.
Keywords: Household income; Financial satisfaction; Ireland